Contemporary political agency : theory and practice - Maiguashca, Bice, 1965-; Marchetti, Raffaele (London : Routledge, 2013)
'This book explores and critically reflects on the theory and practice of political agency in contemporary global politics. In light of the changing relationship between the state, the market and the society, it seeks to map both theoretically and empirically contemporary forms of global political agency. This book reflects on the theory and practice of political agency in contemporary global politics. More specifically, it empirically analyses a range of different forms of political agency and explores their significance for understanding and enacting global politics. Reflecting the efforts of scholars from a variety of disciplines from political theory and Sociology to Geography and International Relations, it brings into conversation a wide spectrum of theoretical approaches including Marxism, feminism, post-structuralism and historical institutionalism. The contributors compare a range of forms of political agency; exploring their significance for the theory and practice of global politics; and reflect on the tensions and synergies generated by recent efforts to conceptualise them.Demonstrating an innovative and interdisciplinary approach Contemporary Political Agency will be of interest to students and scholars of international relations, sociology, political economy and political theory'--
'This book explores and critically reflects on the theory and practice of political agency in contemporary global politics. In light of the changing relationship between the state, the market and the society, it seeks to map both theoretically and empirically contemporary forms of global political agency'--
Includes bibliographical references and index.
Keywords: Political sociology; Social change; Agent (Philosophy).